Constructive-semantic Characteristics of Mother’s Speech as a Factor of Child’s Speech Development - Gudzovskaya, A (KnE Life Sciences, 2018)
Important characteristics of normal mental development of a child are the characteristics of his speech, vocabulary, mastery of grammatical constructions. According to the peculiarities of speech, one can judge the ability of a person to reflect not only the external, perceived properties of objects, but also internal, significant correlations and relationships. In our work, we call these properties constructive and semantic characteristics of speech. The child’s speech develops only in interaction with the people around him, the main figure of which is the mother. The aim of the study was to determine how the constructive and semantic characteristics of the mother’s speech influence the development of the child’s speech, vocabulary and speech activity. The study involved 30 children aged 6.5–7.5 years and their mothers. For diagnostics, the subtest ‘Dictionary’ of the WISC test was used. The traditional method of determining the level of speech development was supplemented by indicators of constructive-semantic characteristics (speech activity, propensity to use different speech structures associated with speech development levels, use of each of the four types of constructions in accordance with the stages of verbal development). Significant connections between individual indicators of the speech of the child and his mother were revealed. Relations allow us to talk about the constructive and semantic characteristics of adult speech as a factor in the development of the child’s speech. The study made it possible to reveal the mechanism of the implicit formation of concepts in the child by generalizing a large number of situational descriptions and features perceived from verbal judgments of the mother. Speech activity of children decreases in the conditions of primary use by the mother of speech structures ‘action with the object’, ‘functional purpose of the objects’. The results obtained make it possible to consider the constructive-semantic characteristics of maternal speech as a factor of the zone of the nearest development of the child’s speech. Keywords: speech development, factors of speech development, speech activity, zone of proximal development, speech behavior as a joint action, constructive semantic characteristics of speech, levels of speech development